PROFIT LEVEL AND PRICE FIXING IN HAZELNUT PRODUCTION - H. Fidan; M. A. Şahinli (Journal of Animal and Plant Sciences, 2010)
Hazelnut is conventional fruit being produced in black sea region of country having the highest production value and export volume in the world. It has been traditionally supported by governments through guarantee purchasing and thus has led hazelnut production and its stock to increase. Producers are making a typical cost that is consisting of fixed and variable costs. Rational producers are seeking income and profit maximization under current economic environment. This study clearly reveals that the country has experienced over production of this product. In this study, data belong to cost and income models collected by survey method. Hazelnut cost and income are linked with establishment information which is provided from 54 agricultural establishments through sampling method. These establishments were selected from density of hazelnut production. In this regard, different organizations have maintained different registers with regards to hazelnut related information. Demand is made by regres over income and price and this point income elasticity of demand and price elasticity of demand are found. lnQd= 4.497+0.000003lnRd–0.17lnPd model is established by log-log models and later, it is found like this income elasticity of demand is 0.000003 and price elasticity of demand is -0.17. Getting empirical results are similar with economical theory. All of the costs details are collected from producers with face to face by survey method.
Keywords: Profit level; price fixing; hazelnut; costs